A comparison of rat models that best mimic immune-driven preeclampsia in humans - Jahan, Fahmida; Vasam, Goutham; Cariaco, Yusmaris; Nik-Akhtar, Abolfazl; Green, Alex; Menzies, Keir J.; Bainbridge, Shannon A. (Frontiers in Endocrinology, 2023)
Preeclampsia (PE), a hypertensive pregnancy disorder, can originate from varied etiology. Placenta malperfusion has long been considered the primary cause of PE.However, we and others have showed that this disorder can also result from heightened inflammation at the maternal-fetal interface. To advance our understanding of this understudied PE subtype, it is important to establish validated rodent models to study the pathophysiology and test therapies. We evaluated three previously described approaches to induce inflammation-mediated PE-like features in pregnant rats: 1) Tumor necrosis factor-ɑ (TNF-ɑ) infusion via osmotic pump from gestational day (GD)14-19 at 50ng/day/animal; 2) Polyinosinic:polycytidylic acid (Poly I:C) intraperitoneal (IP) injections from GD 10-18 (alternate days) at 10mg/kg/day/animal; and, 3) Lipopolysaccharide (LPS) IP injections from GD 13-18 at 20ug-70ug/kg/day per animal.Maternal blood pressure was measured by tail-cuff. Upon sacrifice, fetal and placenta weights were recorded. Placenta histomorphology was assessed using H&E sections.Placenta inflammation was determined by quantifying TNF-ɑ levels and inflammatory gene expression. Placenta metabolic and mitochondrial health were determined by measuring mitochondrial respiration rates and placenta NAD + /NADH content. Of the three rodent models tested, we found that Poly I:C and LPS decreased both fetal weight and survival; and correlated with a reduction in region specific placenta growth. As the least effective model characterized, TNF-ɑ treatment resulted in a subtle decrease in fetal/placenta weight and placenta mitochondrial respiration. Only the LPS model was able to induce maternal hypertension and exhibited pronounced placenta metabolic and mitochondrial dysfunction, common features of PE. Thus, the rat LPS model was most effective for recapitulating features observed in cases of human inflammatory PE.Future mechanistic and/or therapeutic intervention studies focuses on this distinct PE patient population may benefit from the employment of this rodent model of PE.